Pengembangan Modul Pembelajaran Biologi Berbasis Inkuiri Terbimbing pada Materi Ekosistem untuk Siswa Kelas X SMAN 2 Menggala: (Development Of Guided Inquiry-Based Biology Learning Modules On Ecosystem Materials For Class X Students Of SMAN 2 Menggala) - Vienna Restiana; Suhendi Suhendi; Yudiyanto Yudiyanto; Nasrul Hakim (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
The purpose of this study was to determine the characteristics of the guided inquiry-based biology learning module on ecosystem material for class X high school students, to determine the feasibility of the guided inquiry-based biology learning module on ecosystem material for class X high school students, and to find out the responses from biology teachers and students. In terms of the results of the questionnaire assessment. This study uses the Research and Development method developed by Sugiyono to develop printed learning media in the form of modules. Before testing the product, the finished initial product is then validated by experts. The final result of the material expert got a percentage of 86% with the